Analisis Konsep Kota Cerdas dengan Pemanfaatan Internet of Things (IoT) di Kota Palembang - Zainal Abidin; Tata Sutabri; Sugeng Purwanto (Institute of Advanced Knowledge and Science, 2023)
This research analyzes the Smart City Concept with the Use of the Internet of Things (IoT) in the City of Palembang by considering internal factors, which shows a total score of 28 for strengths and 27 for weaknesses. On the other hand, external factors show a value of 34 for opportunities and 26 for threats. The SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats) is used to evaluate strategic positions in facing challenges and exploiting opportunities in implementing the Smart City concept. Next, a TOWS (Threat, Opportunity, Weakness and Strength) analysis was carried out which resulted in an in Palembang City is SO (Strengths – Opportunities), namely utilizing internal advantages to optimize existing opportunities. In conclusion, the most appropriate strategy is to utilize internal strengths to maximize existing opportunities, while reducing the impact of internal weaknesses on external threats. A strong partnership is needed between the government, the private sector and active community participation to realize the vision of an IoT-based Smart City in the City of Palembang.